2018
DOI: 10.3949/ccjm.85a.18095
|View full text |Cite
|
Sign up to set email alerts
|

Influenza update 2018–2019: 100 years after the great pandemic

Abstract: T his year marks the centennial of the 1918 infl uenza pandemic, which killed 50 million people worldwide. Three more infl uenza pandemics and annual epidemics have occurred since then, with other signifi cant interim events (Table 1). 1 The 2017-2018 epidemic was particularly severe and long. 2 This centennial year update focuses primarily on immunization, but also reviews epidemiology, transmission, and treatment. ■ EPIDEMIOLOGY 2017-2018 was a bad season The 2017-2018 infl uenza epidemic was memorable, domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Annual vaccination against influenza is considered as the most important strategy to prevent influenza and reduce the burden of this disease. 6 , 12 It is also known to decrease influenza hospitalizations, complications and death. Moreover, high immunization coverage is seen as a strategy for prevention of an influenza pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual vaccination against influenza is considered as the most important strategy to prevent influenza and reduce the burden of this disease. 6 , 12 It is also known to decrease influenza hospitalizations, complications and death. Moreover, high immunization coverage is seen as a strategy for prevention of an influenza pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Among US adults, less than half of the vaccination target has been achieved. 12 , 20 In the Middle East, annual vaccination coverage is similarly low. 21 …”
Section: Introductionmentioning
confidence: 99%
“…Seasonal influenza viruses (IV) cause yearly infection cycles that tend to peak in the winter in temperate regions and during rainy periods in tropical climates (1). Seasonal IV epidemics create a significant public health burden, with the 2017-to-2018 season resulting in the highest number of deaths since 2010 and >30,000 hospitalizations in the United States alone (2). Seasonal variation in environmental parameters, including relative humidity (RH), has been implicated in the seasonal spread of these viruses (35).…”
Section: Introductionmentioning
confidence: 99%
“…This may be because historically, the need to study this has been limited, given that very few pandemics requiring the mask use have been reported. Accordingly, there is limited literature on prolonged mask use, making it difficult to implement RCTs (63)(64)(65)(66). A non-RCT reported that masks, especially N95 respirators, affected air intake, thereby decreasing the respiratory efficiency and increasing the respiratory burden (61), and this may affect normal life and even be life threatening for vulnerable populations, such as children, pregnant women, the elderly population, and individuals with chronic diseases or those performing highintensity exercise.…”
Section: Summary Of Findingsmentioning
confidence: 99%